What can enzymes of C₄ photosynthesis do for C₃ plants under stress? - Doubnerová, Veronika; Ryšlavá, Helena (Plant science, 2011)
Phosphoenolpyruvate carboxylase (PEPC), NADP-malic enzyme (NADP-ME), and pyruvate, phosphate dikinase (PPDK) participate in the process of concentrating CO₂ in C₄ photosynthesis. Non-photosynthetic counterparts of these enzymes, which are present in all plants, play important roles in the maintenance of pH and replenishment of Krebs cycle intermediates, thereby contributing to the biosynthesis of amino acids and other compounds and providing NADPH for biosynthesis and the antioxidant system. Enhanced activities of PEPC and/or NADP-ME and/or PPDK were found in plants under various types of abiotic stress, such as drought, high salt concentration, ozone, the absence of phosphate and iron or the presence of heavy metals in the soil. Moreover, the activities of all of these enzymes were enhanced in plants under biotic stress caused by viral infection. The functions of PEPC, NADP-ME and PPDK appear to be more important for plants under stress than under optimal growth conditions.
Keywords: Stress, Physiological; Hydrogen-Ion Concentration; Pyruvate, Orthophosphate Dikinase; citrátový cyklus; Plant Proteins; Citric Acid Cycle; Photosynthesis; fotosyntéza; Carbon Dioxide; pyruvátfosfátdikinasa; rostliny; rostlinné proteiny; fyziologický stres; fosfoenolpyruvátkarboxylasa; Malate Dehydrogenase; oxid uhličitý; Plants; Phosphoenolpyruvate Carboxylase; malátdehydrogenasa; koncentrace vodíkových iontů